2020
DOI: 10.1002/ajae.12027
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Effects on Agricultural Exports: Transaction‐Level Evidence from Pakistan

Abstract: This article examines the effects of domestic currency depreciation on agricultural exports from Pakistan including the responses of price and quantity margins. It uses highly disaggregated firm‐level data that contains the exchange rates of the actual currencies of invoicing at the transaction level. The study finds that the currency depreciation positively affects both intensive and extensive margins. The intensive margin increase in agricultural exports operates mainly through prices, whereas the response o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Tang, Lai, & Ozturk (2011) observed that exports and GDP of Asia's four economies are cointegrated, implying that there is a long-run relationship between the variables. Ali (2017) found that exchange rate fluctuation favorably impacted both intensive and extensive margins (IM and EM) in the case of Pakistan between 2000 and 2013. Buguk, Isik, Dellal, & Allen (2003), using an error correction model, highlighted that the exchange rate and its volatility had little effect on Turkish exports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tang, Lai, & Ozturk (2011) observed that exports and GDP of Asia's four economies are cointegrated, implying that there is a long-run relationship between the variables. Ali (2017) found that exchange rate fluctuation favorably impacted both intensive and extensive margins (IM and EM) in the case of Pakistan between 2000 and 2013. Buguk, Isik, Dellal, & Allen (2003), using an error correction model, highlighted that the exchange rate and its volatility had little effect on Turkish exports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In formula (7), κ is the total wealth owned by the investor in the country, S 1 and S 2 are the total shares of all users of the investor at home and abroad, respectively. In order to maximize the income, the investor will adjust the proportion of its asset portfolio according to the principle of the highest interest rate:…”
Section: Portfolio Balancementioning
confidence: 99%
“…Taking the transaction level evidence of Pakistan as an example, the study in [7] puts forward the impact of the exchange rate on agricultural exports, including the response of price and quantity differences. Highly classified company-level data has been used, including the exchange rate of the actual currency of the transaction level invoice.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large volume of published studies describing the role of the agricultural sector and economic growth. The economic development also affects the agricultural industry (Devaux et al, 2018;Bauer and Johnston 2013;Akanbi et al, 2013;Kohler and Ferjani, 2018;Ali, 2017). Abubakar et al (2018) investigated agricultural export performance on the economic growth of Nigeria for the period 1980 to 2016.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While a significant number of studies examined the relationship of the agricultural industry with economic growth, investigating the relationship with other macroeconomic variables is not an exception. One of the important factors identified by the earlier literature is the exchange rate, which affects the agriculture industry (Reaz et al, 2018;Akanbi et al, 2013;Kohler and Ferjani, 2018;Ali, 2017). Mao (2018) investigated the relationship between real exchange rates and agricultural exports to the firm-product-country level with the use of disaggregated panel data of China's food industry.…”
Section: Literature Reviewmentioning
confidence: 99%